Immunodeficiency and the risk of cervical intraepithelial neoplasia 2/3 and cervical cancer: A nested case‐control study in the Swiss HIV cohort study. Issue 7 (20th November 2015) - Clifford, Gary M.; Franceschi, Silvia; Keiser, Olivia; Schöni‐Affolter, Franziska; Lise, Mauro; Dehler, Silvia; Levi, Fabio; Mousavi, Mohsen; Bouchardy, Christine; Wolfensberger, Aline; Darling, Katharine E.; Staehelin, Cornelia; et al.
Abstract : HIV‐infected women are at increased risk of cervical intraepithelial neoplasia (CIN) and invasive cervical cancer (ICC), but it has been difficult to disentangle the influences of heavy exposure to HPV infection, inadequate screening and immunodeficiency. A case‐control study including 364 CIN2/3 and 20 ICC cases matched to 1, 147 controls was nested in the Swiss HIV Cohort Study (1985–2013). CIN2/3 risk was significantly associated with low CD4+ cell counts, whether measured as nadir [odds ratio (OR) per 100‐cell/μL decrease = 1.15, 95% CI: 1.08, 1.22], or at CIN2/3 diagnosis (1.10, 95% CI: 1.04, 1.16). An association was evident even for nadir CD4+ 200–349 versus ≥350 cells/μL (OR = 1.57, 95% CI: 1.09, 2.25). After adjustment for nadir CD4+, a protective effect of >2‐year cART use was seen against CIN2/3 (OR versus never cART use = 0.64, 95% CI: 0.42, 0.98). Despite low study power, similar associations were seen for ICC, notably with nadir CD4+ (OR for 50 vs . >350 cells/μL= 11.10, 95% CI: 1.24, 100). HPV16‐L1 antibodies were significantly associated with CIN2/3, but HPV16‐E6 antibodies were nearly exclusively detected in ICC. In conclusion, worsening immunodeficiency, even at only moderately decreased CD4+ cell counts, is a significant risk factor for CIN2/3 and cervical cancer. Abstract : What's new? Women infected with human immunodeficiency virus (HIV) suffer from precancerous cervical lesions and severe invasive cervical cancer (ICC) at rates that far exceed those of their HIV‐free counterparts. Our case‐control study nested in the Swiss HIV Cohort Study demonstrated the role of immunodeficiency and notably CD4+ cell nadir in the onset of CIN2/3 and ICC. Even moderate declines in CD4+ cell counts substantially increased the risk of cervical intraepithelial neoplasia grade 2/3. The findings emphasize a key role for early HIV detection and combined antiretroviral therapy initiation in cervical cancer prevention for HIV‐infected women.